Prevalence of extended spectrum beta-lactamase and metallo-beta-lactamase genes in imipenem resistant Pseudomonas aeruginosa from admitted patients in a tertiary level hospital, Bangladesh - Kabir, Rubaiya Binte; Jobayer, Mohammad; Farhana, Nasreen; Shamsuzaman, S. M. (International Journal of Research in Medical Sciences, 2024)
Background: Pseudomonas aeruginosa are known for their multiple mutations and rapid acquirement of antimicrobial resistance genes. The presence of metallo-β-lactamase (MBL) is the commonest reason for the treatment failure in carbapenem therapy. Production of extended spectrum β-lactamase (ESBL) in these isolates makes the treatment more challenging. Due to the importance of the carbapenems in resistant infection management, finding the true frequencies of such enzymes is imperative. Methods: A total of 446 samples were collected from the admitted patients with infected burn, surgical wound, and endotracheal tube in situ. Isolation and identification of organisms and antimicrobial susceptibility testing were done by established methods. Identification of P. aeruginosa was confirmed by polymerase chain reaction (PCR). Production of ESBLs was detected phenotypically by double disc synergy, and MBL by double-disc synergy, combined disc, and modified Hodge test. Genes encoding ESBLs and MBLs were detected by PCR. Results: Among the 446 samples, 84.31% yielded growth, from which 232 (61.70%) were P. aeruginosa. Among the P. aeruginosa, 72 (31.03%) were resistant to imipenem. Phenotypically, 57 (79.17%) of these strains were ESBL and all were MBL producers. blaOXA-10 was the most common ESBL encoding gene (29.83%). blaNDM-1 was the most prevalent MBL encoding gene (34.72%). Moreover, 27 (38%) imipenem resistant P. aeruginosa had concurring ESBL and MBL genes. Conclusions: The substantial percentages of ESBL, MBL and simultaneous presence of both genes suggests routine screening of these genes which will provide an opportunity for better selection of antimicrobials in the management of resistant P. aeruginosa.